2023
DOI: 10.1038/s41419-022-05508-y
|View full text |Cite
|
Sign up to set email alerts
|

DDX17 induces epithelial-mesenchymal transition and metastasis through the miR-149-3p/CYBRD1 pathway in colorectal cancer

Abstract: DEAD box helicase 17 (DDX17) has been reported to be involved in the initiation and development of several cancers. However, the functional role and mechanisms of DDX17 in colorectal cancer (CRC) malignant progression and metastasis remain unclear. Here, we reported that DDX17 expression was increased in CRC tissues compared with noncancerous mucosa tissues and further upregulated in CRC liver metastasis compared with patient-paired primary tumors. High levels of DDX17 were significantly correlated with aggres… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 49 publications
(54 reference statements)
0
9
0
Order By: Relevance
“…[9,13] The miR-149 targets different genes and pathways and plays a dual role in proliferation and apoptosis, in some cancers such as leukemia, glioblastoma, prostate, and melanoma, mir-149 is upregulated and acts as an onco-miRNA, but in the lung, and gastric, hepatocellular, colorectal, and breast cancers are downregulated and known as tumor suppressor, [18] some factors such as FOXC1, ADAM12, CYBRD1, and ZBTB2 have been identified as targets of miR-149 to exert its function on cell proliferation and cancer metastases. [7,8,[19][20][21] Cytological experiments have confirmed that miRNA-149 inhibits the biological behavior of GC by targeting FOXC1, [8] but its role in clinical needs to be defined.…”
Section: Discussionmentioning
confidence: 99%
“…[9,13] The miR-149 targets different genes and pathways and plays a dual role in proliferation and apoptosis, in some cancers such as leukemia, glioblastoma, prostate, and melanoma, mir-149 is upregulated and acts as an onco-miRNA, but in the lung, and gastric, hepatocellular, colorectal, and breast cancers are downregulated and known as tumor suppressor, [18] some factors such as FOXC1, ADAM12, CYBRD1, and ZBTB2 have been identified as targets of miR-149 to exert its function on cell proliferation and cancer metastases. [7,8,[19][20][21] Cytological experiments have confirmed that miRNA-149 inhibits the biological behavior of GC by targeting FOXC1, [8] but its role in clinical needs to be defined.…”
Section: Discussionmentioning
confidence: 99%
“…137 DEAD-box helicase 17 (DDX17) is a multifunctional ATP-dependent RNA/DNA helicase that is involved in the initiation and development of a variety of tumours. 138 In NSCLC, the upregulation of DDX17 is associated with increased gefitinib resistance, while the silencing of DDX17 can partially reverse this sensitivity. 139 One study showed that increased DDX17 expression promoted β-catenin transcriptional activity.…”
Section: Gefitinibmentioning
confidence: 99%
“…Despite the initial efficacy of EGFR‐TKIs, approximately 65% of EGFR‐TKI‐sensitive NSCLC patients develop resistance to these medications within 9 to 13 months of treatment 137 . DEAD‐box helicase 17 (DDX17) is a multifunctional ATP‐dependent RNA/DNA helicase that is involved in the initiation and development of a variety of tumours 138 . In NSCLC, the upregulation of DDX17 is associated with increased gefitinib resistance, while the silencing of DDX17 can partially reverse this sensitivity 139 .…”
Section: Roles Of Xpo1 In Drug Resistancementioning
confidence: 99%
“…Moreover, DDX17 was reported to augment cancer-associated features by inhibiting miRNAs. DDX17 can promote EMT and metastasis in colorectal cancer (CRC) by mediating the miR-149-3p/CYBRD1 axis 181 . The expression of the tumor-suppressive miR-149-3p is reduced by DDX17, resulting in increased expression of its target CYBRD1.…”
Section: Dead-box Rna Helicasesmentioning
confidence: 99%